2020
DOI: 10.3390/ijerph17186665
|View full text |Cite
|
Sign up to set email alerts
|

Eating-Disordered Behavior in Adolescents: Associations with Body Image, Body Composition and Physical Activity

Abstract: Eating disorders (EDs) represent a disparate group of mental health problems that significantly impair physical health or psychosocial functioning. The aim of this study was to present some evidence about the prevalence of eating-disordered behavior (EDB) in adolescents, and explore its associations with body image (BI), body composition (BC) and physical activity (PA) in this age group. Data from 780 adolescents participating in a health behavior in school-aged children (HBSC) study conducted in Slovakia in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 43 publications
1
12
0
4
Order By: Relevance
“…Additionally, our study showed that EAT-26 scores increased significantly with BMI. Similar findings were reported previously in Jeddah (8) , Madrid (13) and Slovakia (24) . Being overweight pre-or during adolescence might lead adolescents to adopt disordered eating attitudes to lose excessive weight (32) .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, our study showed that EAT-26 scores increased significantly with BMI. Similar findings were reported previously in Jeddah (8) , Madrid (13) and Slovakia (24) . Being overweight pre-or during adolescence might lead adolescents to adopt disordered eating attitudes to lose excessive weight (32) .…”
Section: Discussionsupporting
confidence: 92%
“…Contrary to our study findings, the prevalence of EDs among adolescents aged 15–18 in Jeddah city, Saudi Arabia, was higher (33 %) ( 8 ) . Additionally, higher prevalences were reported among Slovakian (age: 11–15 years; 37⋅2 %) ( 24 ) and Spanish (age: 13–18 years; 24⋅7 %) ( 13 ) counterparts. However, the prevalence of EDs in our study was higher than among Singaporean (7⋅4 %) ( 25 ) and Ethiopian (6 %) adolescents ( 26 ) .…”
Section: Discussionmentioning
confidence: 97%
“…However, in absolute values, there is a higher percentage in favor of elite female players. Studies have shown that females have more ED behaviors than males [ 43 , 44 , 45 ], often due to socio-cultural impositions and aesthetic patterns, making them a high risk group for the distortion of body self-image and ED [ 46 ]. This trend seems to be repeated in athletes [ 34 ]; furthermore, the results coincide with those of Fortes et al [ 35 ], finding no differences in the EAT-26 between men and women indoor handball players [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In females, as can be seen in the correlations, there was a positive association between EAT-26 total score and BMI, in addition to the one between subscale dieting and BMI. Moreover, some studies found that overweight girls are more likely to present restrictive eating behaviors, worry about their weight and be less satisfied with their appearance [ 44 , 45 ]. On the other hand, in males, the correlations between BMI and total EAT-26 score and BMI and oral control subscale were negative.…”
Section: Discussionmentioning
confidence: 99%
“…Los criterios de exclusión fueron: Artículos no disponibles en texto completo de forma gratuita en la web o a través de la biblioteca de la Universidad Nacional Andrés Bello. Se identifi caron inicialmente 3.985 publicaciones y tras la aplicación de fi ltros (para PubMed se utilizó: idioma [español e inglés], año de publicación [2016-2021], rango etario [6 y 18 años]; para LILACS: idioma [español e inglés], año de publicación [últimos 5 años]; para EBS-CO: año de publicación [en los últimos 5 años]) se obtuvieron 1448 artículos para realizar la lectura de título y resumen (tabla 1), luego se procedió a eliminar artículos duplicados y que cumplían criterios de exclusión, quedando así 38 artículos preseleccionados para lectura de texto completo y evaluación de calidad, de los cuales sólo 9 cumplían todos los requisitos [12][13][14][15][16][17][18][19][20] .…”
Section: Revisiónunclassified